Non-Adiabatic Excited-State Time-Dependent GW (TDGW) Molecular Dynamics Simulation of Nickel-Atom Aided Photolysis of Methane to Produce a Hydrogen Molecule - Aaditya Manjanath; Ryoji Sahara; Yoshiyuki Kawazoe; Kaoru Ohno (Nanomaterials)
Methane photolysis is a very important initiation reaction from the perspective of hydrogen production for alternative energy applications. In our recent work, we demonstrated using our recently developed novel method, non-adiabatic excited-state time-dependent <semantics>GW</semantics> (TD<semantics>GW</semantics>) molecular dynamics (MD), how the decomposition reaction of methane into a methyl radical and a hydrogen atom was captured accurately via the time-tracing of all quasiparticle levels. However, this process requires a large amount of photoabsorption energy (PAE ∼<semantics>10.2</semantics> eV). Moreover, only one hydrogen atom is produced via a single photon absorption. Transition metal atoms can be used as agents for photochemical reactions, to reduce this optical gap and facilitate an easier pathway for hydrogen production. Here, we explore the photolysis of methane in the presence of a Ni atom by employing TD<semantics>GW</semantics>-MD. We show two possibilities for hydrogen-atom ejection with respect to the location of the Ni atom, towards the Ni side or away from it. We demonstrate that only the H ejection away from the Ni side facilitates the formation of a hydrogen molecule with the quasiparticle level corresponding to it having an energy close to the negative ionization potential of an isolated H2 molecule. This is achieved at a PAE of 8.4 eV which is lower compared to that of pristine methane. The results obtained in this work are an encouraging step towards transition metal-mediated hydrogen production via photolysis of hydrocarbons.